Protease activated receptor 4 limits bacterial growth and lung pathology during late stage Streptococcus pneumoniae induced pneumonia in mice - de Stoppelaar, Sacha F.; van ’t Veer, Cornelis; van den Boogaard, Florry E.; Nieuwland, Rienk; Hoogendijk, Arie J.; de Boer, Onno J.; Roelofs, Joris J. T. H.; der Poll, Tom van (Thrombosis and Haemostasis, 2013)
Streptococcus pneumoniae is a common causative pathogen of pneumonia and sepsis. Pneumonia and sepsis are associated with enhanced activation of coagulation, resulting in the production of several host-derived proteases at the primary site of infection and in the circulation. Serine proteases cleave protease activated receptors (PARs), which form a molecular link between coagulation and inflammation. PAR4 is one of four subtypes of PARs and is widely expressed by multiple cell types in the respiratory tract implicated in pulmonary inflammation, by immune cells and by platelets. In mice, mouse (m)PAR4 is the only thrombin receptor expressed by platelets. We here sought to determine the contribution of mPAR4 to the host response during pneumococcal pneumonia. Pneumonia was induced by intranasal inoculation with S. pneumoniae in mPAR4-deficient (par4-/-) and wild-type mice. Mice were sacrificed after 6, 24 or 48 hours (h). Blood, lungs, liver and spleen were collected for analyses. Ex vivo stimulation assays were performed with S. pneumoniae and mPAR4 activating peptides. At 48 h after infection, higher bacterial loads were found in the lungs and blood of par4-/- mice (p < 0.05), accompanied by higher histopathology scores and increased cytokine levels (p < 0.05) in the lungs. Ex vivo, co-stimulation with mPAR4 activating peptide enhanced the whole blood cytokine response to S. pneumoniae. Thrombin inhibition resulted in decreased cytokine release after S. pneumoniae stimulation in human whole blood. Our findings suggest that mPAR4 contributes to antibacterial defence during murine pneumococcal pneumonia.
Keywords: Protease activated receptors; Streptococcus pneumoniae; thrombin; platelet immunology; infectious diseases